2012
DOI: 10.3109/08958378.2012.688885
|View full text |Cite
|
Sign up to set email alerts
|

Implication of PDGF signaling in cigarette smoke-induced pulmonary arterial hypertension in rat

Abstract: Pulmonary artery hypertension (PAH) is a severe disease characterized with progressive increase of pulmonary vascular resistance that finally causes right ventricular failure and premature death. Cigarette smoke (CS) is a major factor of Chronic Obstructive Pulmonary Disease (COPD) that can lead to PAH. However, the mechanism of CS-induced PAH is poorly understood. Mounting evidence supports that pulmonary vascular remodeling play an important role in the development of PAH. PDGF signaling has been demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Zhao and colleagues confirmed PDGF-BB-induced proliferation and survival of pulmonary artery smooth muscle cells and showed that this effect was mediated by JNK pathway activation (166). Moreover, Xing and colleagues demonstrated that PDGF signaling plays a role in cigarette smoke-induced PAH and observed higher expression levels of PDGF-B and PDGFRb in pulmonary arteries of rats exposed to cigarette smoke compared with control rats (167).…”
Section: Pdgf Signaling In Lung Diseasementioning
confidence: 77%
“…Zhao and colleagues confirmed PDGF-BB-induced proliferation and survival of pulmonary artery smooth muscle cells and showed that this effect was mediated by JNK pathway activation (166). Moreover, Xing and colleagues demonstrated that PDGF signaling plays a role in cigarette smoke-induced PAH and observed higher expression levels of PDGF-B and PDGFRb in pulmonary arteries of rats exposed to cigarette smoke compared with control rats (167).…”
Section: Pdgf Signaling In Lung Diseasementioning
confidence: 77%
“…1 Animal experiments demonstrated that chronic cigarette exposure may cause lung parenchyma and airway inflammation, and induce the reconstruction of small pulmonary vessels and small airway, resulting in pulmonary arterial hypertension. 2,3 Previous studies have reported that activation of the renin-angiotensin-aldosterone system (RAAS) system was involved in the pathogenesis of pulmonary vascular remodeling and PAH. 4,5 The expression of angiotensin-converting enzyme (ACE) increased in the pulmonary arterial of patients with PAH.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Cigarette smoke extract significantly increased rat pulmonary artery smooth muscle cell (PASMC) proliferation, which was inhibited by PDGFR inhibitor Imatinib. Thus, their results indicated PDGF signaling is also implicated in CS-induced PH [26].…”
Section: Pulmonary Vascular Endothelial Injury Cellular Growth and Rmentioning
confidence: 94%
“…There were no perinatal death, nine live births and three first-trimester miscarriages. Mean birthweight was 2197 grams, mean gestational age was 34 weeks (range [26][27][28][29][30][31][32][33][34][35][36][37][38][39], and mean birthweight percentile was 36 (range 5-60). Five babies required admission to the neonatal intensive care unit, but were all eventually discharged home.…”
Section: Obstetricsmentioning
confidence: 99%